2001
DOI: 10.1046/j.1365-2036.2001.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological treatment of acute colonic pseudo‐obstruction

Abstract: Acute colonic pseudo-obstruction (Ogilvie's syndrome) can be defined as a clinical condition with symptoms, signs and radiological appearance of acute large bowel obstruction unrelated to any mechanical cause. Recent reports of the efficacy of cholinesterase inhibitors in relieving acute colonic pseudo-obstruction have fuelled interest in the pharmacological treatment of this condition. The aim of the present review is to outline current perspectives in the pharmacological treatment of patients with acute colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
13

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 86 publications
0
103
0
13
Order By: Relevance
“…Appropriate caloric support must be provided by IV infusion. Erythromycin, somatostatin and neostigmine can be used to promote transit and decrease the duration of acute episodes [61][62][63] .…”
Section: Treatment Of the Acute Phasementioning
confidence: 99%
“…Appropriate caloric support must be provided by IV infusion. Erythromycin, somatostatin and neostigmine can be used to promote transit and decrease the duration of acute episodes [61][62][63] .…”
Section: Treatment Of the Acute Phasementioning
confidence: 99%
“…The pathogenesis of Ogilvie's syndrome or ACPO has been explained by Abnormalities of the autonomic nervous system, particularly dysfunction of parasympathetic system and the underlying pathophysiology, whatever the cause, is an early motor disturbance followed by complete impairment of gut peristalsis with progressive dilatation (De Giorgio et al, 2001). However, the pathogenesis of ACPO in patients with SCD is unclear, this is because not only previous studies have shown no evidence of gut ischemia, micro vascular or macro vascular occlusion in these patients but also the disorders associated with acute colonic pseudo obstruction have been ruled out in studied patients and all investigations failed to clarify a cause for this manifestation (Knox-Macaulay et al, 2003).…”
Section: Discussion:-mentioning
confidence: 99%
“…It is a poorly understood syndrome, characterized by symptoms, signs and radiological pattern of the large bowel obstruction with no evidence of mechanical obstruction (De Giorgio et al, 2001;Singh et al, 2005). Typically ACPO occurs in patients with serious illnesses, surgical interventions, infections, burns, trauma and narcotic administration (Gmora et al, 2002).…”
Section: Introduction:-mentioning
confidence: 99%
“…Medical managements include drugs like metoclopramide and neostigmine. Neostigmine (a reversible acetylcholinersterase inhibitor that stimulates the colon) is the best evaluated medical treatment with published success rates of up to 50 per cent of patients [14,15].…”
Section: Discussionmentioning
confidence: 99%